صوفیانہ افکار کی عصری معنویت : متحیرانہ افعال کا تحلیلی جائزہ: The Fruits of Astonishment and Contemplation on the Path of Spiritual Journey - Hafiza Ambreen Fatima; Naveed ur Rehman (International Research Journal of Arabic and Islamic Studies, 2024)
In the realm of the divine, a seeker always receives torrential downpours of theophany. Opposite theophany’s astonishes the seeker. In this mystical journey, the traditional tools of philosophy, wisdom, and logic prove ineffective, yielding to the supreme guidance of love, affection, and humility, which lead the traveler to his ultimate destination. Maulana Rumi, in his renowned work "The Masnavi," meticulously delineates this profound journey, from its inception to its culmination. He offers intricate insights into the intricate mental state of the seeker and a comprehensive exploration of their various attributes. Moreover, Rumi extends his wisdom by presenting a multitude of pathways and methods that assist the seeker in their quest to reach the ultimate spiritual destination.